The spread of the invasive mosquito Aedes albopictus (Diptera: Culicidae) in Portugal: a first genetic analysis - Zé-Zé, Líbia (2024)
Background: Aedes albopictus, commonly known as the Asian tiger mosquito, has become one of the most invasive mosquito species. Over the last 5 decades, it has been introduced and established in various tropical and temperate regions worldwide. First reported in Europe in 1979 in Albania and later in Italy in 1990, the species is now established in 13 European Union (EU)/European Economic Area (EEA) countries and 337 regions (2023). In Portugal, Ae. albopictus was first detected in the Algarve and Penafiel regions in 2017, followed by Alentejo in 2022 and Lisbon in 2023. This mosquito species poses a significant public health risk as a vector for numerous pathogenic viruses, including dengue, Zika, and chikungunya. Methods: Aedes albopictus collected in Lisbon in 2023 were analyzed using cytochrome c oxidase I (COX) gene sequencing to understand their genetic relationships. Results: Our data indicate that the Ae. albopictus mosquito populations detected in three locations in Lisbon in 2023 correspond to recent but distinct introduction events. Conclusions: Although there has been no local transmission of Aedes-transmitted viruses in mainland Portugal to date, the spread of the mosquito and increased international travel increase the risk of Aedes-borne disease outbreaks. The ongoing spread of Ae. albopictus in the country and the confirmed multiple introductions in new locations raise awareness of the need to monitor mosquito vectors to control and prevent autochthonous Aedes-borne disease outbreaks.